Perceived everyday discrimination, socioeconomic status, and mammography behavior - Jessica Vinegar; Marissa Ericson; Lilia Espinoza; Lenna Dawkins-Moultin; Dede K. Teteh-Brooks (Scientific Reports)
Abstract Black women (BW) experience age-adjusted breast cancer mortality rates that are 40% higher than White women. Although, screening rates for breast cancer are similar between White and Black women, differences in mammography utilization exist among women with lower socioeconomic status (SES). Moreover, perceived everyday discrimination (PED) has been shown to have an inverse relationship on health screening behavior among BW. However, mammography behaviors of BW with low SES, who also report higher levels of PED, is not well known. This study aims to explore the relationship between perceived discrimination, SES, and mammography behavior. Participants were recruited between 2020 and 2022 through the Bench to Community Initiative, a community-based participatory research study, and completed a 41-item survey. Logistic regression was used to test the associations of mammography utilization with PED (assessed by a shortened version of the Everyday Discrimination Scale), SES, and race/ethnicity. Most participants (77%) identified as BW (African American, African, and Caribbean) followed by White (17%) and other groups (6%). Many respondents (87%) had health insurance; 67% reported having had a mammogram; and 41% were breast cancer survivors. Most respondents (63%) had a college education and income between $51,000 and $75,000. In an initial logistic regression model, race/ethnicity, income, and PED significantly predicted mammography behavior (χ2 (8) = 45.464, p < .01). In an additional stepwise logistic regression model that controlled for a history of breast cancer, race/ethnicity, income, PED, and education accounted for 35% of mammogram screening behavior (χ2 (12) = 112.410, p < .01). Race/ethnicity, income, education, and PED were associated with mammography behavior. Addressing these social determinants of health factors may improve our understanding of ways discrimination leaves BW vulnerable to disparate health outcomes, including breast cancer.